Geophysics Appearance of The South China Sea - Eddy Mirnanda (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2021)
South China Sea (SCS) is underlain by sediments of an average density 2.10 g/cm3 of 2 km thickness at its central part up to 10 km in the margins. The basement rock is the upper and lower crust of densities 2.67 and 2.85 g/cm3 respectively of varying thicknesses. The thinnest crustal rock is at the centre of SCS that is called the South China Sea Basin (SCSB). The Mohorovicic discontinuity is about 15 km depth below the SCSB. Heatflow values in this basin vary from 2 to 3.5 HFU.Lineations of total magnetic anomaly are generally in a west-east direction covering the whole study area. However, an elongated northeast-southwest lineation of dipole anomaly separates the west-east anomaly patterns in the north from those in the south. This feature is also observed in the gravity map. These elongated patterns of the total magnetic features are in coincident with the occurrences of seamounts inferred being remnant of extinct seafloor spreading. Because of this spreading a crustal extension had taken place that separated Kalimantan from the mainland of China to restore its present position. A paleomagnetic study result confirms this hypothesis.The Palawan trench is marked by north-east trending magnetic and gravity anomaly that is inferred being traces of a remnant subduction zone. This anomaly forms a boundary between the Zengmu also called the Sarawak basin and the SCSB. Here, heat flow value is 1 to 2 HFU. This value in coincident with gravity gradient of 2.5 mGal/km also represents an active subduction of the Manila trench north of the Palawan Island. The Manila trench is supposed to be the energizing source of volcanism and earthquake in the Phillippines. Free-air and Bouguer anomaly of the order of 50 to 60 mGal and magnetic of about 100 nT represent the Zengmu basin in the Sunda Shelf. This basin is underlain by sediments of 2.10 g/cm3 of 8 km thickness and also crustal rock which is much thicker than the one underneath the SCSB. Strong topographic relief at the surfaces of sedimentary layer and the crustal rock is very my much associated with normal faulting that may cause fluctuation of the free-air values.The continental margins of Sarawak and the Sunda Shelf are areas of hydrocarbon deposits now still in production, whereas the offshores Vietnam and Hainan are promising target for hydrocarbon exploration.